Centrosome amplification in chondrosarcomas: A primary cell culture and cryopreserved tumor sample study - Pinheiro, Carla Aparecida (2017)
The genetics background underlying the aggressiveness of chondrosarcoma (CS) is poorly understood. One possible cause of malignant transformation is chromosomal instability, which involves an error in mitotic segregation due to numerical and/or functional abnormalities of centrosomes. The present study aimed to evaluate centrosome amplification in cryopreserved samples of tumor tissue from patients with CS. An analysis was performed on 3 primary cultures of tumors from patients who underwent surgery between January 2012 and December 2012 at the Department of Orthopedics at the Barretos Cancer Hospital (Barretos, Brazil). Additionally, cryopreserved tumor specimens were analyzed from 10 patients. The data were assessed using immunocytochemistry and immunohistochemistry staining techniques with monoclonal antibody anti-gamma-tubulin. A total of 4 samples of CS cultured cells were obtained from 3 patients. A recurrence of a histological grade III tumor was detected in a female patient with Ollier's syndrome. The other 2 cases were grade I and III. The incidence of centrosome amplification in the primary cultures ranged from 15-64% of the cells. Whereas control cultured fibroblasts showed baseline levels of 4% amplified cells. For the cryopreserved specimens, two independent observers analyzed each sample and counted the cells stained with.-tubulin, verifying the percentage of affected cells to be a mean of 14%, with the number of clusters ranging between 0-6 per slide. In conclusion, centrosome amplification was found to be a consistent biological feature of CS and may underlie chromosomal instability in this tumor.